Exploring Student Challenges in Learning Writing Descriptive Text : A Case Study Vocational School in Bekasi - Trastiawan, Rizky Ardianto; Wigati, Fikri Asih; Srisudarso, Mansyur (Journal of Educational Sciences, 2025)
Writing is a fundamental language skill that plays a crucial role in academic and professional success. Descriptive writing, in particular, requires students to vividly portray ideas, experiences, or concepts using words. The purpose of this study is to provide educators and policy makers with valuable insights into targeted interventions to help students overcome barriers and achieve proficiency with writing descriptive. The use of a purposive sampling method ensures targeted selection of participants, taking into account factors such as program specialization. This is achieved by ensuring comprehensive representation of the student population, through a strategic selection of participants who will offer a variety of insights. n conclusion, The teacher uses the "picture to picture" method, where students are asked to observe the picture and its description. Some students who feel confused by the picture to picture method, students find it more difficult to observe and express the characteristics of quiet people, lack of confidence in writing descriptions, limited mastery of English vocabulary and grammar. This causes students to lack confidence in writing descriptions using grammatically correct English.